Skull base imaging, anatomy, pathology and protocols. Issue 1 (24th October 2019) - Quirk, Bernadine; Connor, Steven
Abstract : The skull base is the major bony and soft tissue interface for the intracranial and extracranial compartments. Its anatomy is complex, containing multiple traversing foramina that act as conduits for various neurovascular structures. The optimum imaging modality depends on the specific diagnostic question and area of interest; both CT and MR have complementary roles. This article focuses on the applied compartmental anatomy of the skull base and specific imaging protocols, and discusses the range of pathologies that neurologists will encounter.